Pengaruh Media Audio Visual Terhadap Hasil Pembelajaran Under Ring Permainan Bola Basket di SMAN 3 Karawang Barat - Muhammad Al Hidayatullah; Muhammad Mury Syafei; Akhmad Dimyati (Jurnal Ilmiah Wahana Pendidikan, 2023)
This study aims to test the influence of Audio Visual Media on Learning Outcomes Under Ring Basketball games. the subjects in this study were class XI social studies 1 students with a total sample of 36 people using random sampling. With 10 meetings 2 times including pretest and posttest to measure the initial test and the final test. In conducting the initial test, you can get a pretest score with a score of 533 and a posttest with a total score of 668. The results of this study show that the influence of Audio Visual Media learning on the learning outcomes of Under Ring Basketball games has succeeded in increasing with the resulting t-count being 6,257 and t-table 2,723 with a value of P = 0.000. The results show that the t-count value > t-table and significant probability is less than 0.05. So it can be concluded that there is a noticeable difference between audio-visual learning outcomes and Under Ring abilities in pretest and posttest data. So that the audio visual has a significant impact on the ability of Under Ring basketball games in students of SMAN 3 Karawang